Digital literacy, social interaction, and relative poverty in Chinese households - Li, Xuewen; Wang, Xiaogang (Frontiers in Human Dynamics, 2025)
This study investigates the impact of digital literacy and social interaction on relative poverty among Chinese households, based on the 2020 and 2022 China Family Panel Studies (CFPS) data. Through robust econometric analysis, including quantile regression models and threshold quantile regression models, we examine the direct effects and threshold effects of digital literacy, social interaction on household relative poverty. Our research considers six dimensions, such as income, education, health, living conditions, social security and subjective evaluations, and constructs a household relative poverty index under both national and provincial poverty standards. Our findings indicate that improvements in digital literacy and social interaction contribute to alleviating relative poverty across different poverty lines and quantiles. The enhancement of digital literacy and social interaction significantly supports in improving their relative poverty status, but has a lesser effect on low-poverty-households. There exists a non-linear relationship, with a threshold, between digital literacy and social interaction on household relative poverty. The threshold effect of digital literacy shows a pattern of initial alleviation followed by an increase, while social interaction exhibits an initial increase followed by a decrease. Improvements in education level and marital status, or a reduction in the proportion of children and elderly in a household, can effectively alleviate relative poverty, with a stronger impact on high-poverty-households. These findings highlight the need for understanding of the role of digital literacy and social interaction in relative poverty study, providing empirical evidence for the formulation of more targeted poverty reduction strategies.